FAKTOR YANG MEMPENGARUHI MINAT KARIR MENJADI AKUNTAN PENDIDIK - Ika Kristianti; Robby Setiawan; Dewi Yuliyanti (Universitas Kristen Krida Wacana, 2020)
The purpose of study are to know and analyze factors that influence accounting students on career interest as accounting educator. Some factors that affect the career interest as accounting educator are work experiences, educational background, opportunity cost, and the perception of the profession accounting educator. Primary data in this study is collected by 90 accounting students in Satya Wacana Christian University. Data analyzers used in this study is multiple regression analysis method. Based on the partial test, the hypothesis on the work experience variable is rejected, while for the other three variables, educational background, opportunity cost and perception of accountant profession, are accepted. Keywords: work experience, educational background, opportunity cost, perceptions on the profession as accounting educator and interests on the profession as accounting educator.